2009
DOI: 10.1586/17434440.6.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolds for tendon and ligament repair: review of the efficacy of commercial products

Abstract: Driven by market demand, many biological and synthetic scaffolds have been developed during the last 15 years. Both positive and negative results have been reported in clinical applications for tendon and ligament repair. To obtain data for this review, multiple electronic databases were used (e.g., Pubmed and ScienceDirect), as well as the US FDA website and the reference lists from clinical trials, review articles and company reports, in order to identify studies relating to the use of these commercial scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
348
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(354 citation statements)
references
References 94 publications
2
348
1
Order By: Relevance
“…In addition, the use of allografts is further limited by their higher overall surgical costs; approximately US$ 1,000 extra per clinical case [305,306]. For these reasons, the use of xenografts took off, with numerous products currently available [307,308]. Although positive functional scores and improved movement as early as 6 months post-operation have been reported [309], many studies have demonstrated high failure rates and tearing incidents [310][311][312][313], which may be attributed to processing conditions (e.g.…”
Section: Tissue Grafts -The Top-down Approach For Tendon Repairmentioning
confidence: 99%
“…In addition, the use of allografts is further limited by their higher overall surgical costs; approximately US$ 1,000 extra per clinical case [305,306]. For these reasons, the use of xenografts took off, with numerous products currently available [307,308]. Although positive functional scores and improved movement as early as 6 months post-operation have been reported [309], many studies have demonstrated high failure rates and tearing incidents [310][311][312][313], which may be attributed to processing conditions (e.g.…”
Section: Tissue Grafts -The Top-down Approach For Tendon Repairmentioning
confidence: 99%
“…An expert review by Chen et al [2] discusses the pros and cons of a number of these commercially available medical devices and how they fair surgically.…”
Section: Introductionmentioning
confidence: 99%
“…Acellular tissues are becoming increasingly used as a source for surgical soft tissue reconstruction [1,2,7]. Being freed of cells and cellular components, these scaffolds produce minute antigenicity [2,6,9] and provide a biologic environment for cellular ingrowth and subsequent remodelling.…”
Section: Introductionmentioning
confidence: 99%